Community Efforts of Tutup Ngisor in Maintaining Art and Cultural Traditions - Yohana Ari Ratnaningtyas (Program Pascasarjana, 2018)
The objective of the study is to find out the cause of traditional art in the sub-village of Tutup Ngisor which still survive until now. Qualitative descriptive research is used to reveal data comprehensively in the field. Techniques of data collection are conducted by holding observations of various artistic activities that exist, semi-structured interviews with figures and leader of the arts community as well as studying some literature and previous studies. The results show that interpreting the tradition and change in art is addressed with wisdom, has become a strong foundation for the people of Tutup Ngisor sub-village in maintaining its traditions, maintaining the local values and being wise in facing of outside influences. This research is expected to provide a solution to the possibility of reviving an extinct local tradition and keeping the tradition alive well. Therefore it is necessary to have a good and clear management system in order to anticipate the development of the era so that the art community can continue to grow and develop.Keywords: art community, traditional art that can survive.